FEATURES OF FORMATION OF STUDENTS’ TECHNOLOGICAL COMPETENCE - Rakhimov Zakir Toshtemirovich (PEDAGOGS, 2024)
Abstract. In the article, the formation of technological competence of students, the emergence of social needs for education, the acquisition of certain theoretical and practical knowledge, the awakening of motivation for learning, the acquisition of certain theoretical and practical knowledge, determining the content of students’ learning activities, managing students’ learning activities, psychological to identify the similar and different aspects of the studied objects, to find reliable methods of their identification, to reflect the structure of the studied system in a theoretically developed form, to determine its laws, technological approach conceptual and design, to rapidly develop various fields and aspects of pedagogical and social reality, to make the results more accurate prediction and management of pedagogical processes, analysis and systematization of existing practical experience and its use on a scientific basis, comprehensive solution of educational and social problems, provision of favorable conditions for personal development, reduction of the impact of negative situations on a person, optimal use of available resources, issues of solving upcoming socio-pedagogical problems are interpreted.